PROPOSAL OF MANAGEMENT IN EDUCATIONAL ORIENTATION FOR THE DISTANCE UNIVERSITY SYSTEM (Revista Electrónica Calidad en la Educación Superior, 2017)
The purpose of this article is to present the proposal for an Area of Research, Linkage and Academic Development, with acronyms AIVDA, in the field of educational guidance, accompaniment and student development and research processes of the Fundamental Research Program Distance Education-PROIFED, UNED, Costa Rica. The experience and implementation of an initiative of joint work has allowed to articulate two great spaces in the scope of university management at a distance and the academic strengthening of the student body.  On the one hand, the Vicerrectoría de Investigación; as a framework for academic action and, on the other, the development, application and input of research results in the processes of Educational Orientation; as a framework for student orientation. The AIVDA is integrated as PROIFED Area with contribution and support to the different Programs and services offered by the Office of Orientation and Student Development-OFODE to all students of the University and other academic instances. In its structure the AIVDA: its objectives, conceptual axes and its management actions are contextualized in the field of research in foundations of distance education that favors the development and practice of ─ a theoretical model, a research network and a portfolio of academic projects - linked institutionally and focused on the student population.  A work area that would base their work on the approach of University Social Responsibility and its impact on academic training, research and epistemology as main reference of the Universities in their sphere of influence.